2021
DOI: 10.1016/j.heliyon.2020.e05721
|View full text |Cite
|
Sign up to set email alerts
|

Counter-radicalization policies and policing in education: making a case for human security in Europe

Abstract: Research on counter-radicalization policies and policing in education in Europe is currently patchy and often focused on the United Kingdom. Scholars have observed that counter-radicalization policing in education is a threat to human freedom, human rights and dignity, and safe learning environments. However, scholars generally have not examined this issue from the viewpoint of human security. This paper examines the policing policy matter from the perspective of the personal security form of human security. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…However the condition p 0 > 1 2 does not guarantee R spreading, which requires the additional condition m > m c . With n = 1, it yields m > 1−p 0 p 0 as shown in Figure (2). The Figures show also the same landscape with p 0 as a function of m instead of m as a function of p 0 .…”
Section: The Spread Of Radicalsmentioning
confidence: 56%
See 1 more Smart Citation
“…However the condition p 0 > 1 2 does not guarantee R spreading, which requires the additional condition m > m c . With n = 1, it yields m > 1−p 0 p 0 as shown in Figure (2). The Figures show also the same landscape with p 0 as a function of m instead of m as a function of p 0 .…”
Section: The Spread Of Radicalsmentioning
confidence: 56%
“…In recent decades, religion has been a major source of radicalism with the global spread of Islamism. The large number of related terrorist attacks has led many governments and public agencies to allocate significant resources to implementing counter-radicalization policies [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Camargo and Stein (2022) add that government spending on education and health increases access to credit, reducing poverty and economic growth. Another research from Adebayo (2021) found that state policies have an impact on the educational atmosphere and educational performance in human development. McNeal, Schmeida, and Hale (2007) argue that government policy as a whole is a determinant of the success of economic development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The function of the government is to control activities that occur in the community, including financial activities and human capital development (Ma & Ma, 2011). State policies have an impact on the educational atmosphere and educational performance in human development (Adebayo, 2021). The government acts as a domestic financial controller with a controlling policy (Isabel-Maria, Prado-Lorenzo, & Cuadrado-Ballesteros, 2011).…”
Section: Government Systemmentioning
confidence: 99%
“…Hal demikian didukung oleh peneltitan terdahulu yang dilakukan oleh Laborda (2019) bahwa dalam proses melatih scientific explanantion hal utama yang harus dilatihkan kepada peserta didik adalah kemampuan untuk mampu menenmukan setiap istilah penting sebagai bnetuk penguatan untuk menentukan definisis dalam setiap istilah yang telah mereka temukan (Aldahmash & Omar, 2021;Puzachenko et al, 2021). Lebih lanjut dikatakan bahawa penguatan kognitif peserta didik pada materi pembelajaran Sains (IPA) Ketika mereka mampu mendefinisikan setiap istilah sains yang mereka temukan (Adebayo, 2021;Danovitch et al, 2021) Penguatan materi yang dilakukan oleh peserta didik setelah membca materi pembelajaran akan membuat peserta didik mudah dalam memahami setiap konsep dasar. Selanjutnya memalui sintaks ke dua yakni peta konsep (concept map).…”
Section: Pembahasanunclassified